GROSS MUNICIPAL PRODUCT AS MEASURE OF ESTIMATION OF ECONOMIC POTENTIAL OF ISTRICTS AND CITIES - V. L. Pulyaevskaya; В. Л. Пуляевская (Novosibirsk State University of Economics and Management, 2015)
The article presents the calculation technique of the gross municipal product by institu- tional economy sectors by industries. Methodological principles of sectors generation for the calculation of the gross municipal product by municipal formations are defined. Comparative evaluation of species composition of metropolitan regions and urban districts of Republic of Sakha (Yakutia) for 2010 is given. В статье содержится методика расчета валового муниципального продукта по институциональным секторам экономики по видам экономической деятельности. Определены методологические принципы построения секторов для расчета ВМП по муниципальным образованиям. Приведена сравнительная оценка видовой структуры муниципальных районов и городских округов Республики Саха (Якутия) за 2010 г.